Drying Shrinkage and Gel/Space Ratio of Blended Cement Pastes with Fly Ash - Li, Yan; Sheng Sun, Dao; Sheng Wu, Xiu; Guo Wang, Ai; Xu, Wei; Deng, Min (Asian Journal of Chemistry, 2013)
This paper reports the drying shrinkage and gel/space ratio of blended cement pastes with fly ash. In this study, Portland cement was used as the basic cementitious material. Fly ash was used as cement replacement material. The samples produced from fresh pastes were demoulded after a day; then they were cured at 20 ± 1 ºC with 50 ± 3 % relative humidity until the samples were used for measurement at different ages. The degree of cement hydration of the plain cement pastes was determined by determining the non-evaporable water content. The degree of fly ash reaction in blended cement paste with fly ash was determined using a selective dissolution procedure. The degree of cement hydration in blended cement paste with fly ash was estimated based on the relation between the degree of cement hydration and effective water to cementitious (w/c) ratio. The gel/space ratio of blended cement paste was evaluated based on the degrees of cement hydration and fly ash reaction. The results show that blended cement paste possesses lower the gel/space ratio and drying shrinkage value than that of plain cement paste and the determined gel/space ratio correlates linearly with the data on the drying shrinkage.